2020
DOI: 10.1093/ntr/ntaa024
|View full text |Cite
|
Sign up to set email alerts
|

How Financial Incentives Increase Smoking Cessation: A Two-Level Path Analysis

Abstract: Introduction Financial incentives effectively increase smoking cessation rates, but it is unclear via which psychological mechanisms incentives influence quit behavior. The current study examines how receiving financial incentives for smoking cessation leads to quitting smoking and investigates several mediators and moderators of that relationship. Aims and Methods The study sample consisted of 604 tobacco-smoking employees f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…One study found that the effect of telemedicine for smoking cessation on cessation was mediated by providers’ support, which, in turn, led to increased self-efficacy and impacted cessation [ 28 ]. Another study found that the effect of financial incentives on quitting smoking was mediated only by self-efficacy but not program satisfaction [ 30 ]. The unique value of the current study’s serial mediation model is in demonstrating how treatment engagement leads to higher cessation outcomes [ 7 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study found that the effect of telemedicine for smoking cessation on cessation was mediated by providers’ support, which, in turn, led to increased self-efficacy and impacted cessation [ 28 ]. Another study found that the effect of financial incentives on quitting smoking was mediated only by self-efficacy but not program satisfaction [ 30 ]. The unique value of the current study’s serial mediation model is in demonstrating how treatment engagement leads to higher cessation outcomes [ 7 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results will provide the first known evidence on potential serial mediators of smartphone apps for smoking cessation. While such serial mediational models are useful for developing an in-depth understanding of intervention efficacy, they are rare in smoking cessation research [ 28 - 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have found that the use of financial incentives can be complementary to other stop smoking interventions. A secondary analysis of a cluster randomised trial (n=604) in the Netherlands, for example, found that financial incentives can influence smoking cessation in indirect ways by increasing self-efficacy and medication use, suggesting that incentive-based interventions may best be combined with other smoking cessation methods 25. Moreover, the authors reported an association between positive programme evaluations and a number of psychosocial factors, including ‘higher self-efficacy, more social influence to quit and more positive attitudes about quitting’ 25…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, incentive-based interventions can have mixed results in different populations and implementation ‘may not be transferable from one country to another’ due to differing cultural norms and attitudes towards the use of monetary rewards to change health behaviours 16. Notably, at least one study has reported that the effect of financial incentives did not depend on an individual’s responsiveness to rewards 25…”
Section: Introductionmentioning
confidence: 99%
“…People who received FITs for smoking cessation (vs. nonincentive group) were more likely to have higher rates of smoking cessation program enrollment (Hennrikus et al, 2002), quit attempts, and abstinence (Donatelle et al, 2000;Giles et al, 2014;Halpern et al, 2018;van den Brand et al, 2021;Volpp et al, 2006Volpp et al, , 2009. FITs for continued abstinence through 1year predicted smokers' long-term quit success (van den Brand et al, 2021). Furthermore, the effectiveness of FITs for smoking cessation continues beyond the duration of incentive provision (Notley et al, 2019).…”
mentioning
confidence: 99%